Water and Development : An Evaluation of World Bank Support, 1997-2007, Volume 2. Appendixes - Independent Evaluation Group (Washington, DC: World Bank, 2012)
The amount of available water has been constant for millennia, but over time the planet has added 6 billion people. Water is essential to human life and enterprise, and the increasing strains on available water resources threaten the mission of institutions dedicated to economic development. The ultimate goal is to achieve a sustainable balance between the resources available and the societal requirement for water. In this evaluation the Independent Evaluation Group (IEG) examines all the water-related projects financed by the World Bank between fiscal 1997 and the end of calendar 2007. Bank activities related to water are large, growing, and integrated. They include water resources management, water supply and sanitation, and activities related to agricultural water, industrial water, energy generation, and water in the environment. Through both lending and grants, the World Bank (the International Development Association and the International Bank for Reconstruction and Development, or IBRD) has supported countries in many water-related sectors. This evaluation examines the full scope of that support over the period from fiscal 1997 to the end of calendar 2007. More than 30 background studies prepared for the evaluation have analyzed Bank lending by thematic area and by activity type. The evaluation is by definition retrospective, but it identifies changes that will be necessary going forward, including those related to strengthening country-level institutions and increasing financial sustainability.